Safety and Tolerability, Dose-Escalating, Double-Blind Trial of Oral Mannitol in Parkinson's Disease - Linetsky, Eduard; Abd Elhadi, Suaad; Bauer, Max; Gallant, Akiva; Namnah, Montaser; Weiss, Sagit; Segal, Daniel; Sharon, Ronit; Arkadir, David (Frontiers in Neurology, 2022)
Mannitol, a natural alcoholic-sugar, was recently suggested as a potential disease-modifying agent in Parkinson's disease. In animal models of the disease, mannitol interferes with the formation of α-synuclein fibrils, inhibits the formation of α-synuclein oligomers and leads to phenotypic recovery of impaired motor functions. Parkinson's patients who consume mannitol report improvements of both motor and non-motor symptoms. Safety of long-term use of oral mannitol, tolerable dose and possible benefit, however, were never clinically studied. We studied the safety of oral mannitol in Parkinson's disease and assessed the maximal tolerable oral dose by conducting a phase IIa, randomized, double-blind, placebo-controlled, single-center, dose-escalating study (ClinicalTrials.gov Identifier: NCT03823638). The study lasted 36 weeks and included four dose escalations of oral mannitol or dextrose to a maximal dose of 18 g per day. The primary outcome was the safety of oral mannitol, as assessed by the number of adverse events and abnormal laboratory results. Clinical and biochemical efficacy measures were collected but were not statistically-powered. Fourteen patients receiving mannitol completed the trial (in addition to eight patients on placebo). Mannitol-related severe adverse events were not observed. Gastrointestinal symptoms limited dose escalation in 6/14 participants on mannitol. None of the clinical or biochemical efficacy secondary outcome measures significantly differed between groups. We concluded that long-term use of 18 g per day of oral mannitol is safe in Parkinson's disease patients but only two third of patients tolerate this maximal dose. These findings should be considered in the design of future efficacy trials.